A new strategy for the synthesis of modified novolac resin and its polymer/clay nanocomposite - R. Mohammad-Rezaei; B. Massoumi; M. Eskandani; M. Abbasian; M. Jaymand (eXPRESS Polymer Letters)
A novel epoxy nanocomposite composed of epoxidized novolac (ENR), epoxidized polystyrene (EPSt), and nanoclay was fabricated and characterized successfully. For this purpose, the novolac was epoxylated using a substitution nucleophilic reaction between hydroxyl group of novolac and chlorine group of epichlorohydrin. The EPSt was synthesized through the oxidizing of an allylated PSt (All-PSt). A mixture of ENR (70 wt%), EPSt (20 wt%) and Cloisite®R 20A (5 wt%) was cured using ethylenediamine (EDA; 5 wt%) to afford a C-ENR-EPSt/clay nanocomposite. The transition electron microscopy (TEM) as well as powder X-ray diffraction (XRD) analysis revealed that the fabricated nanocomposite has an exfoliated structure. As the thermal property studies results, the addition of EPSt as well as Cloisite® 20A has synergistic effect on the thermal stability of the ENR resin.